DESIGN AND FABRICATION OF SUGARCANE LIFTING MACHINE - Shashikant D. Thorat1, Pranav M. Bhandare2, Yogesh S. Autade3, Vinayak S. Gawali4; B. P. Ronge; K. S. Pukale; Prof. Sahebgauda (International Journal of Innovations in Engineering Research and Technology, 2022)
India is one of the major agricultural countries in the world. Maharashtra is a major sugarcane cultivating state had the majority of labors for the lifting of sugarcane manually, but that was the situation 10- 20 years back. Today, as the demand for sugarcane products like sugar has increased, the cultivation of sugarcane is also increased. But as there has been a shortage of labor for the sugarcane lifting process, sugarcane which is ready for lifting is left as it is in the field and dried which affects its quality & quantity of sugar content in it due to delay in supplying to the sugarcane industry. The process of lifting consists of cutting the cane from the bottom, then cutting off its top leaves, making a bundle which consists of 10 to 15 canes each and then carrying it to the trucks and loading it.